1995
DOI: 10.1164/ajrccm.151.1.7812552
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular advancement splint: an appliance to treat snoring and obstructive sleep apnea.

Abstract: Snoring and obstructive sleep apnea (OSA) are related to narrowing of the upper airway. A mandibular advancement splint (MAS) could improve both conditions by increasing oropharyngeal and hypopharyngeal dimensions. The effects of a MAS on snoring and OSA was evaluated 3.5 +/- 2.1 (mean +/- SD) mo after issue in 57 subjects with habitual loud snoring, 39 of whom had an apnea-hypopnea index (AHI) > or = 10. Assessment was by questionnaire (all subjects) and polysomnography (51 subjects, 47 male) including measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
0
12

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(118 citation statements)
references
References 0 publications
12
94
0
12
Order By: Relevance
“…Although snoring is a hallmark symptom of OSA, it is rarely measured objectively, and there is no standard method to do so. In this study, snoring intensity was objectively measured with an audiometer placed 1 m from the mouth, a technique similar to that used by previous groups [28,29]. Analysis was performed using the maximum for NREM and REM stages of sleep, with the area under the curve and the % sleep time >50 dB; therefore, the recordings are believed to be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Although snoring is a hallmark symptom of OSA, it is rarely measured objectively, and there is no standard method to do so. In this study, snoring intensity was objectively measured with an audiometer placed 1 m from the mouth, a technique similar to that used by previous groups [28,29]. Analysis was performed using the maximum for NREM and REM stages of sleep, with the area under the curve and the % sleep time >50 dB; therefore, the recordings are believed to be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of exacerbating the sleep-related breathing disorder by mandibular advancement splint therapy has been previously reported and indeed is the reasoning behind undertaking a follow-up objective assessment. 23,32,33 Mandibular advancement splints are thought to act by increasing the size and/or reducing the collapsibility of the pharyngeal airway. 15 Cephalometric predictors have been suggested where a favourable response to MAS therapy can be expected 15 but the technique at best only provides a two-dimensional image.…”
Section: Two Of the Most Commonly Used Measures In Assessing Treatmenmentioning
confidence: 99%
“…Objective reduction in snoring by way of a decrease in the number of snores per hour, time spent snoring and mean sound level across the night has been demonstrated. 23,24 The study by Johnston et al 22 demonstrated the mandibular advancement splint as being significantly more effective than a placebo in reducing the frequency and loudness of snoring.…”
Section: Introductionmentioning
confidence: 99%
“…39 Bolstering these results are additional studies which have shown that the oral appliances decrease the AHI by more than half and improve both arterial oxygen saturation and sleep quality in approximately 50% of patients with SAHS. [40][41][42] Removable mandibular repositioning devices are constructed so that the lower jaw …”
Section: Dental and Surgical Managementmentioning
confidence: 99%